World geography of travel and tourism a regional approach - Lew, Alan A.; Hall, Colin Michael, 1961-; Dallen, Timothy J. (Oxford : Butterworth-Heinemann, 2008)
"World Geography of Travel and Tourism addresses the need to understand the cultural, environmental, historical and political context in which international tourism takes place. The expert author team has included major themes and issues in tourism, and positioned them in a regional context. In this way, this text takes a major step into a more analytic approach to global tourism while still providing a clear account of the geography of travel and tourism." "World Geography of Travel and Tourism makes vital reading for any student seeking an introduction to tourism geography and indeed, international tourism and global geography as a whole."--BOOK JACKET.
The Americas.
Includes bibliographical references and index.
All age.
Keywords: Tourism